Kohesi Sosial Tradisi Baroah pada Etnis Dayak Kanayatn di Desa Sungai Laki Kecamatan Mempawah Hulu Kabupaten Landak - Ridal, Hendrik; Ramadhan, Iwan; Utami, Patrisia Rahayu; Wiyono, Hadi; Astari, Zuri (Universitas Tanjungpura, 2025)
This study examines social cohesion in the Baroah tradition of the Dayak Kanayatn community in Sungai Laki Village, Mempawah Hulu District, Landak Regency. The Baroah tradition is one of the local wisdoms of the Dayak Kanayatn tribe, which holds a meaning as an expression of gratitude to Jubata (God) for an abundant rice harvest, as well as serving as a symbol of community togetherness. The purpose of this study is to describe how aspects of mutual cooperation, social relations, and active community participation are manifested in the implementation of the Baroah tradition as a form of social cohesion. This study employs a qualitative descriptive approach, utilising data collection techniques that include observation, interviews, and documentation. The informants consisted of one traditional leader and four local residents, selected through purposive sampling. Data were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, with data validity ensured through triangulation of sources and techniques. The results of the study indicate that social cohesion is reflected through mutual cooperation during the preparation and implementation of the event, social relations through interactions with others, and active community participation in helping to assist in the implementation. The Baroah tradition serves as a unifying force, binding the community together while preserving the cultural identity of the Dayak Kanayatn ethnic group.